Risk Factors that Influence the Incidence of Diarrhea in Toddlers - Pellondou, Kurnia Bend. Yunita; Lede, Meldy Emry Handany; Tefa, Stefania Efenhilda (CV. Global Health Science Group, 2024)
Diarrhea is a condition where the frequency of defecation is more than 4 times in babies and more than 3 times in children. The incidence of diarrhea is closely related to the clean and healthy living behavior carried out by family members and the increase in cases is strongly influenced by an unclean environment. This research is to analyze the effect of breastfeeding, nutritional status, and hand washing behavior on the incidence of diarrhea in the Naioni Health Center Work Area, Kupang City. Method: This research uses an analytical survey method with a cross sectional design. The population in this study was 1,120 toddlers in the Naioni Community Health Center Working Area. The sampling technique in this research is cluster random sampling with a sample size of 92 people. Statistical analysis of the data used in this research was the chi square test. Analysis found that variables related to the incidence of diarrhea in toddlers were breastfeeding (pvalue=0.005:RP=3.778), nutritional status (pvalue=0.347:RP=0.589), hand washing behavior (pvalue=0.009:RP=3.429. The incidence of diarrhea which has the greatest impact on toddlers is because of the attention of the community in their life activities to be able to use appropriate water for eating, drinking and other basic human needs and how how to manage food properly and correctly.